Prediction of the Potential Active Compounds in Cucumber (Cucumis sativus L) against Hypertension using Pharmacological Network (Cytoscape) - Camelia Maktur; Febrial Hikmah (Journal of Food and Pharmaceutical Sciences, 2026)
Hypertension is the leading cause of heart disease, kidney failure and stroke in Indonesia. Antihypertensive drugs have proven effective in managing blood pressure levels. However, long-term use of these medications may lead to side effects, reduce patient compliance and increased healthcare costs. Various studies have reported the cucumber (Cucumis sativus L) effect in controlling blood pressure. The purpose of this study is to investigate the molecular basis of these effects and identify the specific pathways involved. This research is a systematic review in silico network pharmacology analysis to forecast the antihypertensive potential of cucumber derived active compounds. By employing computational methods to explore plant-based therapeutic effects, the study identified bioactive components and their targets through the ChEMBL database, followed by protein validation using the Open Targets Platform. The findings contribute to the growing evidence that cucumber plants may play a role in hypertension management through multi-target mechanism.